2021
DOI: 10.1017/s0031182021000962
|View full text |Cite
|
Sign up to set email alerts
|

The people vs science: can passively crowdsourced internet data shed light on host–parasite interactions?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…The iNaturalist database currently contains over 92 million observations of over 344,300 species from across the globe. This valuable resource is being increasingly used in scientific research, and these studies demonstrate consistent results between community- and scientist-collected data [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. A previous analysis found that iNaturalist data concerning important tick and mosquito vectors correlated well with known geographical distributions and seasonality of these species [ 59 ].…”
Section: Introductionmentioning
confidence: 84%
“…The iNaturalist database currently contains over 92 million observations of over 344,300 species from across the globe. This valuable resource is being increasingly used in scientific research, and these studies demonstrate consistent results between community- and scientist-collected data [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. A previous analysis found that iNaturalist data concerning important tick and mosquito vectors correlated well with known geographical distributions and seasonality of these species [ 59 ].…”
Section: Introductionmentioning
confidence: 84%
“…Secondary data from citizen science are often combined with iEcology or culturomics data sources (Jarić et al., 2020) or museum collections (Box 2). Examples include a dietary study of African snakes (Maritz & Maritz, 2020), arthropod parasitism by hairworms (Doherty et al., 2021) and the distribution of anther‐smut disease in the Caryophyllaceae plant family (Kido & Hood, 2020).…”
Section: Secondary Data Are Slowly Diffusing Into the Scientific Lite...mentioning
confidence: 99%
“…There are also other approaches which make use of existing resources from which ecological interactions can be sampled, such as image repositories (i.e. Google images or iNaturalist; Doherty et al, 2021) and text scraping from web pages (Jarić et al, 2020).…”
Section: G Lobal Ecolog Ic Al Ne T Work Datamentioning
confidence: 99%